The Role of the Garut Police Traffic Dikyasa Unit in Preventing Traffic Accidents Among High School Students Through the Goes to School Police Program - Al Faiz, Rizky Rendi Aufa (Police Studies Review, 2024)
The occurrence of traffic accidents that occur in students, especially among high school students, is the background of this research carried out in the jurisdiction of Garut District Police. In connection with this it has an impact on the dynamics of community life. This has led to the impression that the role of the Dikyasa Unit has not been seen in carrying out community education activities especially through the Police Goes To School program in preventing traffic accidents. The purpose of this study is to describe the role of the Special Unit in implementing community education and then through the Police Goes To School program, and to know the factors that influence the implementation of the Police Goes To School program. The focus of the research is the Police Goes To School program conducted by the Garut Police Unit Dikyasa Unit. Data obtained through interviews, observations, and study documents. This study uses a qualitative approach with field research methods. This research uses the concept of community education then, Dikyasa unit concept, management theory, and role theory. This research resulted in the finding that it was still not well targeted to coordinate between the school and the Dikyasa Unit so that the implementation of the community health program then did not work properly and there were still members of the Dikyasa Unit who had not yet implemented the Dikas Dikmas Specific Dikbang so that it affected the quality of the members in its implementation. The influencing factors are supportive such as infrastructure that is available in good condition. There are inhibiting factors such as lack of human resources in quality and quantity. It is necessary to increase the quality of human resources in terms of quality and quantity, it is also necessary to do the education not only by targeting students but also parents, because it is important for the family’s role in supporting the achievement of education goals in the Police Goes To School program.